A superhard titanium alloy and preparation method thereof

By adding specific elements to the titanium alloy and heat treatment, multi-metal compounds are formed, which solves the problem of taking into account both the hardness and molding performance of titanium alloy, and the preparation of superhard titanium alloy is realized, which significantly improves the hardness and maintains the molding performance, expands the Application scope.

CN115874083BActive Publication Date: 2024-12-17YANGZHOU TAIBO MEDICAL EQUIP TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211649284.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2024-12-17
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Titanium alloys have low hardness and poor wear resistance, which limits their widespread use in industrial applications. Existing methods to improve hardness often affect the forming performance of the material.

Method used

A super hard titanium alloy is used, containing 1.25%-23% iron, 0.1%-20% copper, 0.1%-20% silver and 0.5%-15% manganese. It is smelted and heat treated by vacuum smelting and heat treatment. , form multi-metal compounds such as Fe-Ti-Cu, Fe-Ti-Mn or Fe-Ti-Ag to increase the hardness of the alloy, and at the same time control the phase composition and structure of the alloy.

Benefits of technology

It significantly improves the hardness of titanium alloy to 540-670HV, while maintaining the molding performance of the material. It is suitable for casting molding, forging and cold rolling molding. The elements are simple and the smelting process is convenient, which expands the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115874083B_ABST
    Figure CN115874083B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of titanium alloy industry, and discloses a superhard titanium alloy material and a preparation method thereof. The superhard titanium alloy contains 1.25%-23% iron by weight, and also contains one or more of copper, silver, and manganese, and the rest is titanium and other inevitable impurity elements. Through phase transformation strengthening and nano second phase dispersion strengthening, ultra-high hardness is obtained, and the wear resistance of the titanium alloy is improved. The preparation process of the superhard titanium alloy includes: smelting and ingot forming, deformation processing and heat treatment. Superhard titanium alloy can effectively improve the wear resistance of titanium alloy and expand the scope of use of titanium alloy. This patent can be applied to titanium alloy castings, and can also be applied to deformed titanium alloy profiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of titanium alloy industry, and in particular to a superhard titanium alloy and a preparation method thereof. Background Art

[0002] Titanium alloys have very good specific strength and specific stiffness characteristics, as well as corrosion resistance, so they are widely used in various industries. At the same time, titanium alloys have good biocompatibility and are also widely used in medical implants. However, the hardness of titanium alloys is relatively low, and the wear resistance is relatively poor compared to steel, which limits the application of titanium alloys to a certain extent.

[0003] The hardness of pure titanium is generally around 180HV. Even the fourth-grade pure titanium with a higher oxygen content has a hardness of only 220HV, which is much lower than the hardness of stainless steel. Through alloying treatment, such as adding Al and V elements to titanium, it develops into a dual-phase Ti 6 Al 4 V titanium alloy, its hardness can be increased to 280HV-300HV.

[0004] To improve the hardness of metal, we can generally start from the following aspects:

[0005] 1) Increase the content of oxygen, nitrogen and carbon in titanium alloys. For example, increasing the carbon content in steel can significantly increase the hardness of the steel, and increasing the carbon content in cobalt alloys can also increase the hardness of the alloy. Increasing the oxygen content in titanium can also significantly increase the hardness of titanium alloys. Although increasing the oxygen content can increase the hardness to a certain extent, it will also lead to a serious decrease in plasticity. Considering the plasticity of the material, the increase in hardness is limited. GB / T 3620.1-2016, Titanium and Titanium Alloy Grades and Chemical Compositions, points out that the oxygen content of grade 4 pure titanium (TA4) reaches 0.4%, and the hardness value obtained still does not exceed 280HV.

[0006] 2) Form or add a hard second phase in the titanium alloy. For example, in "Sun Liang, Microstructure Regulation and Wear Resistance of In-situ Self-generated (TiC+TiB) Reinforced Titanium-based Composites, Master's Thesis of Shenyang University of Technology, 2018", TiC ceramic particles and TiB are added to the alloy. 2 Particles can also significantly increase the hardness of the alloy. For example, by adding TiC particles, the hardness of titanium alloy can reach 55HRC (600HV). However, this method also has certain shortcomings, that is, the deformation performance of the material is seriously reduced after adding ceramic particles, and it is impossible to form a profile.

[0007] 3) Add alloying elements to change the phase composition in the alloy. For example, adding Al and V elements to titanium to obtain an α+β dual-phase structure can also achieve a higher hardness, which can reach 300HV. Patent application number CN201610247237.9, a method for preparing a high-strength and high-hardness alloy, provides a complex alloy system. After deformation and heat treatment, a Rockwell hardness (HRC) of 45-56 (about HV440-606) can be obtained. However, this method selects more than 7 alloying elements, and the smelting is very complicated and the composition control is difficult.

[0008] Selecting alloying elements and adjusting the hardness of the alloy through phase change does not affect the forming properties of the alloy. It is easy to use and has a wide range of applications. It is a conventional method to improve the mechanical properties of alloys. However, the alloy systems currently reported are very complex. In addition, while improving the hardness of titanium alloys, it is necessary to take into account the forming properties of the alloy at the same time to facilitate subsequent casting, forging, hot rolling and cold rolling. Therefore, taking into account the forming properties of the alloy, developing a superhard titanium alloy material is very important to expand and improve the industrial application of titanium alloys. Summary of the invention

[0009] Aiming at the industrial application of titanium alloy, the present invention designs a superhard titanium alloy and provides a preparation method of the superhard titanium alloy, which can significantly improve the wear resistance of the titanium alloy and can be applied to various industries.

[0010] The technical solution of the present invention is: a super-hard titanium alloy, containing 1.25%-23% iron by weight, and also containing one or more elements of copper, silver, and manganese, and the rest are titanium and other inevitable impurity elements, the weight percentage of oxygen element does not exceed 0.3%, and the total weight percentage of metal elements other than titanium does not exceed 30%.

[0011] The weight percentage of the iron element is 2.6%-10%.

[0012] The weight percentage of the copper element is 0.1%-15%.

[0013] The weight percentage of the copper element is 2.0%-10%.

[0014] The weight percentage of the silver element is 0.1%-20%.

[0015] The weight percentage of the silver element is 5%-10%.

[0016] The weight percentage of the manganese element is 0.5%-15%.

[0017] A method for preparing a superhard titanium alloy, wherein the final casting or profile is obtained through the following process:

[0018] 1) Melting and ingot casting: The super-hard titanium alloy is melted by vacuum melting technology according to the above composition to make the alloy composition uniform, and then cast into an ingot or directly form a casting.

[0019] 2) Deformation processing: For profiles, deformation processing is required, such as profiles, bars, plates and other profiles. Deformation processing includes hot forging, hot rolling and cold rolling. Different processing methods are used according to the specifications of the final material.

[0020] 3) Heat treatment; Heat treatment directly controls the phase composition and organizational structure of the alloy, so it is crucial. Heat treatment is divided into high-temperature heat treatment and low-temperature heat treatment, which are carried out in sequence. Among them, the purpose of high-temperature heat treatment is mainly to homogenize the chemical composition of the alloy, and at the same time completely dissolve the Fe, Cu, Mn and Ag elements in the alloy into the titanium matrix to achieve solid solution strengthening. The temperature is high, the solid solution rate is fast, and the solid solution is sufficient, but the grain growth of the alloy is serious. Therefore, the high-temperature heat treatment temperature is not lower than 750°C, the time is not more than 10 hours, and the cooling rate is not lower than 80°C / s. Increasing the temperature of high-temperature heat treatment can accelerate the complete dissolution of alloy elements in the matrix and shorten the time.

[0021] Preferably, the high temperature heat treatment temperature is not less than 905°C, the time is not more than 6 hours, and the cooling rate is not less than 100°C / s.

[0022] The goal of low temperature heat treatment is to control the phase composition of the alloy, so that Fe, Cu, Mn and Ag elements are precipitated in the form of nanometer or submicron ternary compounds, so as to achieve second phase dispersion strengthening and improve the hardness of the alloy. The low temperature heat treatment temperature is not higher than 700℃ and the time is not more than 40 hours.

[0023] Preferably, the low-temperature heat treatment temperature is not higher than 399° C., and the time is not more than 40 hours.

[0024] Fe is a Beta-Ti stabilizing element that can change the phase composition of the alloy, adjust the hardness of the alloy, and can also be dissolved in the Beta phase to increase the hardness of the alloy. However, when the Fe content is lower than the eutectoid composition, it is difficult to form a second phase to increase the hardness of the alloy. Even if the TiFe phase is precipitated within the hypereutectoid composition range, the hardness cannot be increased due to the low hardness of the TiFe phase.

[0025] Cu, Ag and Mn are alloying elements of titanium alloys, and they are fast eutectoid elements. Therefore, Ti can be precipitated during the solidification or heat treatment of titanium alloys. 2 Cu, TiMn or Ti 2Ag, improves the hardness of the alloy. When the alloy contains Fe and one of Cu, Ag and Mn, the fast eutectoid Cu, Ag or Mn will form one or several ternary metal compounds of Ti-Fe-Cu, Ti-Fe-Ag or Ti-Fe-Mn with Fe and Ti. If the alloy solidification process, deformation process or heat treatment process is controlled, these intermetallic compounds become Fe-Ti-Cu, Fe-Ti-Mn or Fe-Ti-Ag ternary metal compounds of micron, submicron or nanometer size. These compounds have high hardness and can significantly improve the hardness of the alloy.

[0026] The hardness of the alloy is closely related to the volume fraction of the multi-metal compound formed. The higher the volume fraction of the multi-metal compound, the higher the hardness of the alloy. The volume fraction of the multi-metal compound is not only related to the content of the alloying elements, but also closely related to the subsequent heat treatment. The higher the content of the alloying elements, the higher the volume fraction of the multi-metal compound formed. By adjusting the heat treatment process and adopting high temperature and low temperature heat treatment, not only the morphology of the multi-metal compound can be changed, but also the volume fraction can be adjusted. Therefore, the hardness of the alloy can be adjusted by adjusting the chemical composition and heat treatment system of the alloy. However, when the content of the multi-metal compound is sufficient, the hardness value of the alloy will not continue to increase, and the hardness may even decrease due to the formation of binary compounds such as TiFe with lower hardness, and the alloy plasticity will be deteriorated. Therefore, it is necessary to control the alloying elements and quantity in the alloy to obtain an alloy material with excellent comprehensive mechanical properties.

[0027] Beneficial effects of the present invention: The HV hardness of the superhard titanium alloy proposed by the present invention can reach 540-670HV, while taking into account the forming performance of the alloy, which is convenient for subsequent casting, forging, hot rolling and cold rolling. Moreover, the required element types are simple and available, the smelting process is simple, and the forming control is convenient; in addition, since the smelting casting and subsequent forging processes are selected to control the impurity elements of the alloy, especially the oxygen content, the application range of the alloy is wider and broader. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The present invention discloses a microstructure of a superhard titanium alloy.

[0029] Figure 2 This is a high-magnification microstructure diagram of the Ti-Fe-Cu super-hard titanium alloy, which is used to show that a large amount of hard second phase is formed inside. DETAILED DESCRIPTION

[0030] Example

[0031] The designed titanium alloy is prepared according to the chemical composition, and the burnout of the alloy elements is appropriately considered. The burnout amount varies according to the different smelting conditions. Vacuum smelting ensures that the chemical composition of the alloy is uniform. Then casting is performed. For the subsequent profile requirements, the corresponding deformation processing is performed, and then heat treatment is performed to obtain the final alloy material. The hardness test measures the Vickers hardness of the alloy according to national standards. Detailed data is shown in Table 1. According to this method, a super-hard titanium alloy with a HV hardness of 540-670HV can be obtained.

[0032] It can be found from Examples 1-8 that an increase in the Fe content leads to an increase in the hardness of the alloy, and the increase in the hardness value caused by the increase in the Fe content is relatively limited.

[0033] Examples 9-12 are compared with Examples 2, 3, 5, and 7 respectively to prove that the hardness of the alloy increases after adding copper. And through Examples 10, 13-15, it can be proved that as the copper content increases, the hardness of the alloy also increases. Through the comparison of Examples 16-17 with Examples 9 and 12, it is proved that the total content of iron and copper elements cannot exceed 30%, which will cause the hardness of the alloy to decrease significantly.

[0034] Examples 18-21 are compared with Examples 2, 3, 5, and 7, respectively, to prove that the addition of silver can effectively increase the hardness of the alloy. According to the comparison of Examples 19, 22-24, it is proved that as the content of silver in the alloy increases, the hardness of the alloy also increases. Examples 25-26 are compared with Examples 18 and 22, respectively, to prove that the total content of iron and silver cannot exceed 30%, which will cause the hardness of the alloy to decrease.

[0035] Examples 27-30 are compared with Examples 2, 3, 5, and 7, respectively, to prove that the hardness of the alloy can be increased by adding manganese. Examples 28, 31-33 are compared to prove that the hardness of the alloy increases with the increase of manganese content. Examples 34 and 35 are compared with Examples 28 and 27, respectively, to prove that the total content of manganese and iron in the alloy cannot exceed 30%.

[0036] Compared with Examples 13.14.23.24, Example 36.37 proves that the addition of quaternary elements can lead to higher hardness of the alloy. Compared with Examples 38 and 39, Example 36.37 proves that the total content of iron, copper and silver elements cannot exceed 30%. Compared with Examples 13.14.31.32, Example 40.41 proves that the hardness of adding quaternary elements is higher. Compared with Example 42.43 and Example 40.41, it proves that the total content of iron, copper and manganese elements cannot exceed 30%. Compared with Example 44.45 and 23.24.31.32, it proves that the hardness of adding quaternary elements is higher. Compared with Example 46.47 and 44.45, it proves that the total content of iron, silver and manganese elements cannot exceed 30%. Compared with 36.37.38.39.40.41, Example 48.49 proves that the hardness of penta-element is also high. Example 50.51 proves that the content of the penta-element cannot exceed 30%.

[0037] Comparison between Example 48 and Example 52 proves that changes in temperature will cause changes in hardness. High-temperature and long-term heat treatment will lead to a decrease in hardness. Compared with Example 53, Example 48 shows that high-hardness titanium alloy material cannot be obtained if the high-temperature heat treatment temperature does not reach 750°C. Compared with Example 54, Example 48 shows that the low-temperature heat treatment temperature cannot be higher than 700°C, otherwise the hardness of the alloy will be significantly reduced. Compared with Example 55, Example 48 shows that as long as heat treatment is carried out within the scope of the present invention, a high-hardness alloy will be obtained.

[0038] Table 1 Comparative parameters of various embodiments

[0039]

[0040]

[0041]

[0042] In Table 1: *850°C / 5h+cooling rate 120°C / s+600°C / 10h means heating at 850°C for 5 hours, then cooling at a cooling rate of 120°C / s, and then heating at 600°C for 10 hours, and the subsequent steps are the same.

Claims

1. A superhard titanium alloy, characterized in that: The super-hard titanium alloy contains 2.6%-10% iron by weight, and also contains one or more elements of copper, silver and manganese, and the rest are titanium and other inevitable impurity elements; the weight percentage of oxygen in the impurity elements does not exceed 0.3%; the total weight percentage of metal elements other than titanium does not exceed 30%; the weight percentage of the copper element is 0.1%-15%; the weight percentage of the silver element is 5%-10%; The final casting or profile is obtained through the following processes: 1) smelting and ingot forming; 2) deformation processing; 3) heat treatment; first high-temperature heat treatment, then low-temperature heat treatment; the high-temperature heat treatment temperature is not less than 750°C, the time is not more than 10 hours, and the cooling rate is not less than 80°C / s; the low-temperature heat treatment temperature is not higher than 399°C, and the time is not more than 40 hours; The hardness of the super-hard titanium alloy reaches 540-670HV.

2. The superhard titanium alloy according to claim 1, characterized in that: The weight percentage of the copper element is 2.0%-10%.

3. The superhard titanium alloy according to claim 1 or 2, characterized in that: The weight percentage of the manganese element is 0.5%-15%.

4. The superhard titanium alloy according to claim 3, characterized in that: The high temperature heat treatment temperature is not less than 905°C, the time is not more than 6 hours, and the cooling rate is not less than 100°C / s.

Citation Information

Patent Citations

  • A kind of preparation method of high-strength and high-hardness alloy

    CN105671366B

  • Processing method for improving strength and plasticity of copper-containing titanium alloy

    CN112481567A

  • Titanium-copper-iron alloy and associated thixoforming method

    EP3382047A1

  • Hydrogen storage alloy thin film body and its manufacture

    JP1989240629A

  • TiFeCu-BASED ALLOY AND ITS MANUFACTURING METHOD

    JP2013234374A